Evaluasi Program Pelatihan Berbasis E-Learning pada Karyawan Magang Marketing PT. X Tahun 2023 - Nathasya Femi Ekarista; Iwan Sukoco; Sari Usih Natari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Training for intern employees is a crucial component in human resource development within the company. The objective of the research to be achieved is to evaluate the effectiveness of the e-learning training program for marketing interns at PT. X. The research subjects include four individuals: one HRD Development staff, one mentor, and two training participants involved in the Magang Belajar Kampus Merdeka (MBKM) internship program at company X, batch 5, for the period from August to December. The researcher employs a qualitative method. Data sources consist of direct information and information from other parties. Data collection techniques include documentation, observation, and interviews. The triangulation used comprises source triangulation and technique triangulation. The research was conducted in East Jakarta from August 2023 to July 2024. The research findings indicate that PT X has taken positive steps to realize reaction evaluations concerning the willingness to participate in the training program, preparation of the materials to be used, and the motivation of the training participants. In terms of learning stage evaluation, PT X also has clear training objectives, a well-structured learning process, effective material delivery, and significant skill enhancement. Regarding behavioral stage evaluation, PT X has made an impact through behavioral changes, behavioral comparisons, and assessments after the training process, all of which have shown positive trends. This evaluation demonstrates that PT X's program effectively enhances participants' understanding and motivation through interactive methods and flexible access, although the heavy workload needs to be addressed.